2017
DOI: 10.1016/j.bpj.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Reversible Separation of Living, Unperturbed Cell Membranes into Two Liquid Phases

Abstract: Controversy has long surrounded the question of whether spontaneous lateral demixing of membranes into coexisting liquid phases can organize proteins and lipids on micron scales within unperturbed, living cells. A clear answer hinges on observation of hallmarks of a reversible phase transition. Here, by directly imaging micron-scale membrane domains of yeast vacuoles both in vivo and cell free, we demonstrate that the domains arise through a phase separation mechanism. The domains are large, have smooth bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 56 publications
3
89
0
Order By: Relevance
“…In addition, because lipid domains (rafts) play important roles in the association of proteins and membranes, controlling the formation of lipid domains by changing air gas concentrations may enable tuning of the amounts of membrane‐associated proteins in a lipid vesicle. Recently, Rayermann et al reported reversible membrane domain separation of yeast vacuoles by controlling ambient temperature across the transition temperature . The results of the present work suggest that air gas concentrations, especially N 2 concentration, may also be used to affect domain formation on vesicle membranes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In addition, because lipid domains (rafts) play important roles in the association of proteins and membranes, controlling the formation of lipid domains by changing air gas concentrations may enable tuning of the amounts of membrane‐associated proteins in a lipid vesicle. Recently, Rayermann et al reported reversible membrane domain separation of yeast vacuoles by controlling ambient temperature across the transition temperature . The results of the present work suggest that air gas concentrations, especially N 2 concentration, may also be used to affect domain formation on vesicle membranes.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, Rayermann et al reported reversible membrane domain separation of yeast vacuoles by controlling ambient temperature across the transition temperature. [42] The results of the present work suggest that air gas concentrations, especially N 2 concentration, may also be used to affect domain formation on vesicle membranes.…”
Section: Discussionmentioning
confidence: 64%
“…Significant theoretical and experimental evidence supports the influence of lipid composition on membrane curvature, phase partitioning, and nanoscale domains in vesicular budding processes (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Many of the same observations and conclusions most likely also hold in biological processes involving membrane proteins, which complicate the picture still further.…”
Section: Discussionmentioning
confidence: 97%
“…However, molecular dynamic simulations have revealed nanoscopic microdomains of hexagonally packed saturated lipids 30 that may correspond to the nonideal demixing revealed by FRET 31 . Recently a fungal vacuole was reported to exhibit temperaturedependent lipid phase demixing 32 but no function has yet been ascribed to these domains. The specific role of lipid asymmetry and composition, and its role in domain formation and maintenance, in the face of lipid transport, remain to be investigated for any MCS or membrane domain.…”
Section: Discussionmentioning
confidence: 99%